PENINGKATAN PEMBELAJARAN GRAMATIKA DAN HASIL BELAJAR BAHASA JERMAN TENTANG FAMILIE DENGAN METODE STATIONENLERNEN - Ekowati Septi Rahayu (Badan Perencanaan Pembangunan Daerah Kota Magelang, 2020)
The mastery of foreign languages in the era of globalization is very necessary because language will open the horizons of the world of education. One of the foreign languages studied in high school (SMA) and equivalent is German Language. In the learning process, problems will always arise because there are certain levels of difficulty in learning a foreign language. One of the problems that occurred was the problem in class XI IPA 6 of SMA Negeri 1 Magelang. The problem is that students have difficulty in mastering German grammar. The purpose of this study is to improve grammar learning and German learning outcomes in class XI IPA 6 SMA Negeri 1 Magelang. The method used in this study is the Stationenlernen method. The results of this study indicate that there is a change in the learning atmosphere, the previously monotonous learning atmosphere becomes more fun, students are more motivated in the learning process, teachers are more active because they are facilitators, and students are more active because they are involved in group work in a team to work on problems at each station. This study consisted of 2 cycles, namely the cycle applied in meetings 1 to 2. The average results of the repeat scores in the initial conditions were 77.8. In the first cycle the average value was 84.1, while in the second cycle the average value was 88. The conclusion of this study was that there was an increase in students' grammar and learning achievement. This can be seen from the acquisition of values that increase at each meeting.